(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article presents studies on the theoretical and methodological issues of assessing the solvency of business entities, the economic content of the concepts of solvency and creditworthiness, and the relationship between solvency and other economic indicators, and draws conclusions as a result.